Does severe vitamin D deficiency impact obstetric outcomes in pregnant women with thyroid autoimmunity? - AKDENİZ, ESRA (TAYLOR & FRANCIS LTD, 2020)
Purpose: Vitamin D plays an important role in the modulation of the immune system and anti-autoimmune activities. Autoimmune thyroid diseases related to endocrine disorders are associated with poor obstetric outcomes in pregnancy. Herein, we aimed to investigate the contribution of vitamin D hypovitaminosis to poor pregnancy outcomes in pregnant women with the positive autoimmune antibody. Materials and methods: This was a prospective case-control study that enrolled pregnant women at their first trimester. The pregnant women were divided based on thyroid antibody (TA) status (TA-positive pregnant group (TAs (+)) and negative group (TAs (-)). Vitamin D status was categorized as sufficient, insufficient, and deficient (severe and moderate). Results: A total of 283 pregnant women were enrolled in this study. A total of 219 pregnant women were assigned to the TAs (-) group and 64 to the TAs (+) group. The rate of vitamin D insufficiency was 8.7, and 7.8% in the pregnant with TAs (-), and the pregnant with TAs (+) groups, respectively. Vitamin D deficiency was highly prevalent in all groups. Specifically, the prevalence rate was 91 and 92% in the pregnant with TAs (-) and the pregnant with TAs (+) groups, respectively. Admission to the neonatal intensive care unit (NICU) was more prevalent in the pregnant with TAs (+) group than in the pregnant with TAs (-) group (40.6 versus 25%; p = .0187; effect size (ES) = 0.134). The rate of gestational diabetes mellitus (GDM) was significantly higher in the pregnant women with TAs (+) group than that in the pregnant women with TAs (-) group (12.5 versus 4.1%; p = .03; ES =0.13). The rate of NICU admission and GDM was significantly higher in the severe vitamin D-deficient pregnant group with TAs (+) than that in the severe vitamin D-deficient pregnant group with TAs (-) (47 versus 23%; p = .007; ES =0.207 and 19.4% versus 4.1%; p = .006; ES =0.214, respectively). Conclusions: Severe vitamin D deficiency may contribute to increase the prevalence of GDM and need for NICU admission in pregnant women with positive TA.
Keywords: Autoimmunity; pregnancy; pregnancy outcomes; thyroid globulin antibody; thyroid peroxidase antibody; vitamin D; GESTATIONAL DIABETES-MELLITUS; D INSUFFICIENCY; ASSOCIATION; DISEASE; RISK; PATHOGENESIS; PREVALENCE; ANTIBODIES